THE PLACE AND FEATURES OF THE NATIONAL POLICE IN THE SYSTEM OF ENTITIES PROVIDING PUBLIC SECURITY AND ORDER AT THE REGIONAL LEVEL (Bulletin of criminological association of Ukraine, 2023)
The article emphasizes that under martial law, the police faced new security, organizational and regulatory challenges, the solution of which is complicated in the period of ongoing reform. At the same time, on the basis of effective management decisions made in conditions of uncertainty, but aimed at achieving clear results, additional funding for police bodies and units was provided, new information systems for documenting war crimes were introduced, adaptation of individual units to the performance of service and combat tasks and real combat clashes with the enemy was ensured, a number of functions were performed in de-occupied and close-to-the-zone territories for the evacuation of the population, delivery of humanitarian aid, etc. It is proven that determining the features of the police in the system of subjects of ensuring public security and order at the regional level is quite difficult due to the fact that these features are related to different spheres of society's life, and are also dynamically changing under martial law. It is argued that the fundamental features of the police in the system of subjects of ensuring public safety and order at the regional level include the close relationship of the police with other law enforcement agencies, media, local governments, enterprises, institutions and organizations; taking into account the specifics of a particular region from an institutional or organizational point of view; specific preparation for such activities, which is achieved through the functioning of higher education institutions with specific training conditions that train police officers.
Keywords: place; features; National Police; system of subjects of ensuring public safety and order; regional level; historical formation; specifics of the region; interaction; training